2008
DOI: 10.1128/jvi.02407-07
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Microdomains Containing Vesicular Stomatitis Virus M Protein Are Separate from Microdomains Containing G Protein and Nucleocapsids

Abstract: Immunogold electron microscopy and analysis were used to determine the organization of the major structural proteins of vesicular stomatitis virus (VSV) during virus assembly. We determined that matrix protein (M protein) partitions into plasma membrane microdomains in VSV-infected cells as well as in transfected cells expressing M protein. The sizes of the M-protein-containing microdomains outside the virus budding sites (50 to 100 nm) were smaller than those at sites of virus budding (approximately 560 nm). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 58 publications
(61 reference statements)
6
49
0
Order By: Relevance
“…and then M (membrane bound green circles) is incorporated to these microdomains (IV.) as recently shown (195). The role for P, in particular residues 191 to 200, in assembly has been reported recently and it may be involved in steps III.…”
Section: Vsv Assemblymentioning
confidence: 72%
See 4 more Smart Citations
“…and then M (membrane bound green circles) is incorporated to these microdomains (IV.) as recently shown (195). The role for P, in particular residues 191 to 200, in assembly has been reported recently and it may be involved in steps III.…”
Section: Vsv Assemblymentioning
confidence: 72%
“…It has been shown that cytosolic and membrane bound M can bind to RNPs but the proteins have a higher affinity for RNPs isolated from virus versus cytosolic RNPs (57). These observations suggested that M binding to RNPs is dependent on a change in cytosolic RNPs at the plasma membrane and recent evidence has led to a model where G and RNPs associate in microdomains at budding sites and then M is incorporated (195). Treating purified VSV virions with detergent at low ionic strength solubilizes the viral membrane and G protein liberating the highly condensed, tightly coiled skeleton which consists of the RNP and M protein (153,154).…”
Section: Formation Of Skeletons By Mmentioning
confidence: 87%
See 3 more Smart Citations